Strong Convergence Theorems by Hybrid Methods for Two Noncommutative Nonlinear Mappings in Banach Spaces. (26th July 2020) - Takahashi, Wataru; Yao, Jen-Chih
Abstract: In this paper, using the hybrid method defined by Nakajo and Takahashi, we first obtain a strong convergence theorem for two noncommutative generic skew generalized nonspreading mappings in a Banach space. Next, using the shrinking projection method defined by Takahashi, Takeuchi and Kubota, we prove another strong convergence theorem for the mappings in a Banach space. Using these results, we get new strong convergence theorems by the hybrid method and the shrinking projection method in a Hilbert space and a Banach space.